Contribution of the Dr Lech Wierusz Lubuskie Rehabilitation-Orthopaedic Centre in Świebodzin to the development of rehabilitation in Poland - Jandziś, Sławomir; Zaborniak, Stanisław (European Journal of Clinical and Experimental Medicine, 2011)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The author based on archival materials, numerous articles in professional journals and newspapers presented the activities of one of the oldest orthopedic rehabilitation centers in Poland and its influence on the development of medical rehabilitation, orthopedics and sports of disabled people in our country. He described the primary activity, organizational and research achievements and staff training.